Micro-dynamics in regional transition paths to sustainability - an analysis of organizational and institutional change in Augsburg's transition topology - Simone Strambach; Gesa Pflitsch (Philipps-University Marburg, Department of Geography, 2016)
While there has recently been an increased interest in urban and regional transitions to sustainability, there are little profound insights about the emergence, design and enforcement of regional transition paths to sustainability (RTPS). The latter are characterized by organizational and institutional dynamics that affect multiple regimes and cannot fully be captured with the niche-regime categories of the multilevel perspective (MLP). This paper is therefore based on recent approaches from evolutionary economic geography (EEG) that focus on how actors at the microlevel use the plasticity of paths to enact change. The transition path and underlying micro-dynamics over more than 30 years in the Augsburg region revealed in an empirical study are visualized in the form of a transition topology. The results show that RTPS are not a determined process which follows a prescribed course of events from the beginning. Actors use the interpretative flexibility of institutions and establish organizational proximity between different institutional logics to break up institutional consolidations and allow new configurations within the path.
Keywords: B52; D83; Q01; R11; 330; Sustainability transitions; regional paths; institutional change; organizational change; micro-dynamics